KONSEPTUALISASI PARIWISATA BERWAWASAN LINGKUNGAN DALAM PERSPEKTIF GREEN ACCOUNTING (STUDI KASUS TAMAN NASIONAL BANTIMURUNG) - Tenriwaru Tenriwaru; Nur Syamsiah U; Kirana Ikhtiari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The tourism sector, especially ecotourism, has a responsibility to the surrounding environment. This study aims to determine the implementation of green accounting to realize ecotourism based on sustainable development goals (SDGs) in Bantimurung Bulusaraung National Park. Research data were obtained from primary data and secondary data. The method used is a qualitative method with an interpretive approach, as well as testing the validity of the data based on triangulation of data sources carried out at Bantimurung Bulusaraung Nature Tourism. The results of the study found that currently Bantimurung Bulusaraung Nature Tourism is being developed into ecotourism. The carrying capacity of the environment is very important in ecotourism. Efforts are being made to preserve the physical and biological components, including applying the concept of environmental carrying capacity in ecotourism areas. The existence of Bantimurung Bulusaraung Nature Tourism increases the income of the community around the destination. Bantimurung Bulusaraung Nature Tourism has not implemented green accounting, so it has not disclosed environmental costs in detail in the notes to the financial statements. The application of green accounting in the ecotourism sector needs to be implemented because the operational activities of tourism objects are responsible for nature and the surrounding environment. Development of natural tourism in Bantimurung Bulusaraung based on SDGs. Whenever you create a building, the main thing you pay attention to is the environment. Management always measures the level of damage in Bantimurung Bulusaraung Nature Tourism every time they carry out construction.